Influence of sex on sympathetic vasomotor outflow responses to passive leg raising in young individuals - Keisho Katayama; Kana Shiozawa; Jordan B. Lee; Natsuki Seo; Haruna Kondo; Mitsuru Saito; Koji Ishida; Philip J. Millar; Ryoichi Banno; Shigehiko Ogoh (Journal of Physiological Sciences)
Abstract The purpose of this study was to clarify sex differences in the inhibition of sympathetic vasomotor outflow which is caused by the loading of cardiopulmonary baroreceptors. Ten young males and ten age-matched females participated. The participants underwent a passive leg raising (PLR) test wherein they were positioned supine (baseline, 0º), and their lower limbs were lifted passively at 10º, 20º, 30º, and 40º. Each angle lasted for 3 min. Muscle sympathetic nerve activity (MSNA) was recorded via microneurography of the left radial nerve. Baseline MSNA was lower in females compared to males. MSNA burst frequency was decreased during the PLR in both males (− 6.2 ± 0.4 bursts/min at 40º) and females (− 6.5 ± 0.4 bursts/min at 40º), but no significant difference was detected between the two groups (P = 0.61). These results suggest that sex has minimal influence on the inhibition of sympathetic vasomotor outflow during the loading of cardiopulmonary baroreceptors in young individuals.